2008
DOI: 10.1128/aem.02026-07
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of DNA as a Sole Source of Phosphorus, Carbon, and Energy by Shewanella spp.: Ecological and Physiological Implications for Dissimilatory Metal Reduction

Abstract: The solubility of orthophosphate (PO 4 3؊ ) in iron-rich sediments can be exceedingly low, limiting the bioavailability of this essential nutrient to microbial populations that catalyze critical biogeochemical reactions. Here we demonstrate that dissolved extracellular DNA can serve as a sole source of phosphorus, as well as carbon and energy, for metal-reducing bacteria of the genus Shewanella. Shewanella oneidensis MR-1, Shewanella putrefaciens CN32, and Shewanella sp. strain W3-18-1 all grew with DNA but di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
128
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(135 citation statements)
references
References 58 publications
7
128
0
Order By: Relevance
“…DNA was the main component of orthophosphate diester in aquatic macrophytes and algae in Tai Lake. DNA also could be an important source of P in aquatic environments especially when orthophosphate concentrations were small (Pinchuk et al 2008). They were degraded less than DNA, polyphosphate, and phospholipids, but they were rapidly mineralized under anaerobic conditions.…”
Section: Naoh-edta Extractable P From Aquatic Macrophytes and Algaementioning
confidence: 99%
“…DNA was the main component of orthophosphate diester in aquatic macrophytes and algae in Tai Lake. DNA also could be an important source of P in aquatic environments especially when orthophosphate concentrations were small (Pinchuk et al 2008). They were degraded less than DNA, polyphosphate, and phospholipids, but they were rapidly mineralized under anaerobic conditions.…”
Section: Naoh-edta Extractable P From Aquatic Macrophytes and Algaementioning
confidence: 99%
“…Discussion eDNA occurs in significant amounts in terrestrial and aquatic environments where it may serve as important nutrient reservoirs, particularly for nitrogen and phosphorus (Deflaun et al, 1986;Paul et al, 1991;Niemeyer and Gessler, 2002;Dell'Anno and Danovaro, 2005). Accordingly, a previous study showed that Shewanella species are capable of using DNA as source of phosphorus, nitrogen, carbon and energy (Pinchuk et al, 2008). Here we demonstrate that, in addition, eDNA has a major role in surface attachment and development of threedimensional structures during S. oneidensis MR-1 biofilm formation.…”
Section: Mutants Lacking the Prophages Are Defective In Biofilm Formamentioning
confidence: 99%
“…[40,48] In a series of mesocosm experiments using radioactive labelled orthophosphate, adenosine triphosphate (ATP) and DNA, Løvdal et al [49] showed that, even though orthophosphate was the preferred P substrate for bacteria and algae, both ATP and DNA were utilised in mesocosms where orthophosphate was also present. In mesocosms without added orthophosphate the turnover time for dissolved DNA decreased by a factor of 10 (from 15.6 to 1.5 h) with no liberation of free orthophosphateindicating a tight coupling between hydrolysis and uptake.…”
Section: Quantificationmentioning
confidence: 99%
“…However, most studies attribute DNA breakdown to a suite of extracellular enzymes including phosphatase and nucleases. [40,41] Abiotic hydrolysis facilitated by mineral phases [42] is potentially an alternate pathway for the degradation of DNA in aquatic ecosystems -but it has not been demonstrated. The only abiotic degradation pathway that has been demonstrated to date is the breaking of DNA double strands induced by radiation from dissolved uranium.…”
Section: Quantificationmentioning
confidence: 99%
See 1 more Smart Citation